2013 Annual IEEE India Conference (INDICON) 2013
DOI: 10.1109/indcon.2013.6726094
|View full text |Cite
|
Sign up to set email alerts
|

Study of electrical properties of poly-3-alkylthiophen (P3AT) derivatives P3HT, P3BT and P3DDT based field effect transistors

Abstract: Top contact organic thin-film field effect transistors based on regioregular poly(3-butylthiophene-2,5-diyl) (P3BT), poly(3-dodecylthiophene-2,5-diyl) (P3DDT) and poly(3-hexylthiophene-2,5-diyl) (P3HT) of similar concentration were fabricated by spin coating technique. The current-voltage (I-V) characteristics of these three different polymer based organic field-effect transistors (OFETs) were studied. The device performance parameters for each kind of OFET were estimated with the help of measured electrical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…"Research showed that P3HT properties such as optoelectronic properties and crystallinity and its OSCs performance can be altered by modification of its end groups" [8]. "Higher mobility in P3HT FET was as a result of selforganizing nature of the P3HT molecules by thin film deposition, thus, P3HT coated channel film was more crystalline in nature compared to others which improved the conductivity as well as carrier mobility of the film" [9]. "Interestingly, many experimental and theoretical studies have been carried out in the synthesis and applications of poly(hexylthiophene-2,5-diyl) and its derivatives including Density Functional Theory and Time-Depended Density Functional Theory.…”
Section: Introductionmentioning
confidence: 99%
“…"Research showed that P3HT properties such as optoelectronic properties and crystallinity and its OSCs performance can be altered by modification of its end groups" [8]. "Higher mobility in P3HT FET was as a result of selforganizing nature of the P3HT molecules by thin film deposition, thus, P3HT coated channel film was more crystalline in nature compared to others which improved the conductivity as well as carrier mobility of the film" [9]. "Interestingly, many experimental and theoretical studies have been carried out in the synthesis and applications of poly(hexylthiophene-2,5-diyl) and its derivatives including Density Functional Theory and Time-Depended Density Functional Theory.…”
Section: Introductionmentioning
confidence: 99%